PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM DESA SIAGA AKTIF OLEH PEMERINTAH DESA PANGAUBAN KECAMATAN BATUJAJAR KABUPATEN BANDUNG BARAT - Elina Mubarokah (Jurnal Caraka Prabu, 2018)
The title of this research is "Community Empowerment through Active Alert Village Program by the Pangauban Village Government, Batujajar District, West Bandung Regency". The phenomenon in this study saw the optimal Community Empowerment through the Active Alert Village Program by the Pangauban Village Government, Batujajar District, West Bandung Regency. The research method that researchers use is descriptive research methods with a qualitative approach. The technique of determining the informants used was purposive sampling technique. The results of this study indicate that the implementation of the Active Alert Village Program by the Pangauban Village Government has been optimal, it can be seen from (1) Building relationships with related parties regarding health empowerment, cooperation and coordination have been well and sustainable. A sense of empathy is well established through mutual cooperation between communities. (2) How to build communication that is manifested is more focused on people who have actively participated in the Active Alert Village Program (3) are involved in problem solving in strengthening community participation has gone well, the community has been involved in decision making and evaluation. (4) Reflecting the attitudes and values ​​of the social work profession, there is no form of discrimination in the application of the Active Alert Village program.